Advances in Silicon Solar Cells (Springer International Publishing, 2018)
This book provides a review of all types of silicon solar cells. The scope includes monocrocrystalline Si solar cells, polycrystalline and amorphous thin-film silicon solar cells, and tandem solar cells. Production, treatment and development of these devices are reviewed. Limitations of these devices, design optimization, testing and fabrication methods are covered. In addition, current status and future prospects for the further development of silicon solar cells are addressed. Special emphasis is given to methods of attaining high efficiency and thereby cost-effective solar power. The aim of the book is to provide the reader with a complete overview about the recent advances in the structure and technology of all generations of silicon solar cells. .